Ultrahigh resolution imaging of local structural distortions in intergrowth tungsten bronzes. - Kirkland, A; Sloan, J; Haigh, S (2007)
Details of the local structure of a complex tungsten bronze, K(x)WO(3) have been determined using focal series exit wave reconstruction. Octahedral rotations in different structural regions of the same crystal have been directly measured from the exit wave phase and correlated with variations in cation occupancy determined from the exit wave modulus.